Cone-Beam Computed Tomography and Magnetic Resonance Imaging in Temporomandibular Joint Disorder Diagnosis: A Comparative Study - Zhang M; Sang J; Yang C; Liu H; Xiao Y; Li J; Li G (Journal of Multidisciplinary Healthcare)
Manli Zhang, Junzhi Sang, Chunpeng Yang, Haiyan Liu, Yang Xiao, Jinfeng Li, Guangwei Li Department of Imaging, The Second Affiliated Hospital of Qiqihar Medical College, Qiqihar, People’s Republic of ChinaCorrespondence: Guangwei Li, Email utvn862@163.comObjective: This study aimed to investigate the imaging characteristics of temporomandibular joint disorder (TMD) using cone-beam computed tomography (CBCT) and magnetic resonance imaging (MRI), and to compare their diagnostic performance.Methods: Clinical data from 53 TMD patients and 53 healthy controls were retrospectively reviewed. All participants underwent both CBCT and MRI within a two-week interval. Key measurements included condylar dimensions and joint space assessments. The study evaluated each modality’s ability to detect TMD-related abnormalities in the temporomandibular joint (TMJ) and masticatory muscles, such as joint space narrowing, bone changes, disc displacement, and muscle pathology. Statistical analysis compared diagnostic findings between the imaging techniques.Results: Image quality was comparable between CBCT and MRI (P > 0.05). Both modalities showed no significant differences in superior and anterior joint spaces between TMD and control groups, but the posterior joint space, condylar width, and anteroposterior diameter were significantly different (P < 0.05). Across all participants, significant differences were observed between CBCT and MRI measurements for superior and anterior joint spaces (P < 0.05). Among TMD patients, 69.81% had pain disorders and 30.19% had joint disorders. Both modalities demonstrated high inter- and intra-observer consistency (P < 0.05). CBCT showed high agreement for most bony abnormalities but only moderate for disc and muscle pathology. MRI had high agreement for most findings but was moderate in detecting bone hyperplasia and sclerosis. MRI detected significantly more soft tissue abnormalities, including disc displacement and joint effusion (P < 0.05), while CBCT was more effective in identifying bone hyperplasia, sclerosis, and condylar deformation (P < 0.05).Conclusion: Both CBCT and MRI are highly valuable tools for differentiating and assessing TMD. CBCT excels in evaluating bone-related changes, whereas MRI is superior for assessing the articular disc and soft tissue abnormalities.Keywords: cone-beam ct, magnetic resonance imaging, temporomandibular joint disorder, imaging characteristics, comparative study